2006
DOI: 10.1590/s0103-84782006000200041
|View full text |Cite
|
Sign up to set email alerts
|

Níveis das vitaminas A e E em dietas de frangos de corte de 1 a 42 dias de idade

Abstract: INTRODUÇÃOVitaminas são elementos orgânicos essenciais aos homens e animais, e devem ser fornecidas pelos alimentos, uma vez que estes não podem produzir adequadas quantidades por si só. Elas são essenciais para o crescimento, saúde, reprodução e sobrevivência, estando envolvidas na maioria dos processos metabólicos e têm papel critico no ciclo de Krebs (JENSEN, 1974). Por este motivo, elas deverão estar presentes nas rações animais, em pequenas quantidades, causando em sua falta, problemas diversos de desenvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…Vitamins also act as immunomodulators in the endogenous metabolism for improving immune function and resistance to infection in poultry and other domestic animals (Kraemer et al, 2008 formula, about 0.1 to 0.5% on average though correspond from 1 to 3% of the total cost of feed, and the vitamins E and A may amount to 50% of the total cost of the vitamin supplement (Toledo et al, 2006). The requirements of fat-soluble vitamins (A, D, E and K) are those that vary most between recommended and adopted commercial levels.…”
Section: Vitamin In the Feed For Broilers And Ways Of Supplymentioning
confidence: 99%
“…Vitamins also act as immunomodulators in the endogenous metabolism for improving immune function and resistance to infection in poultry and other domestic animals (Kraemer et al, 2008 formula, about 0.1 to 0.5% on average though correspond from 1 to 3% of the total cost of feed, and the vitamins E and A may amount to 50% of the total cost of the vitamin supplement (Toledo et al, 2006). The requirements of fat-soluble vitamins (A, D, E and K) are those that vary most between recommended and adopted commercial levels.…”
Section: Vitamin In the Feed For Broilers And Ways Of Supplymentioning
confidence: 99%
“…Their requirements are low, but if they are not met, the antioxidant system may be compromised, causing serious consequences for the animal's metabolism (SURAI et al, 2006). Vitamin E plays several roles in the body, affecting meat quality, cellular respiration and nucleic acid metabolism, and also acting as a potent antioxidant for unsaturated fatty acids and vitamin A (TOLEDO et al, 2006). Suhajda et al (2000) reported that since the association of selenium with vitamin E was established, along with the modulating effect of glutathione peroxidase and antioxidants on the actions of free radicals and peroxides, the investigation of these elements has intensified.…”
Section: Introductionmentioning
confidence: 99%
“…Como a maioria das vitaminas não é sintetizada em quantidades suficientes para atender a demanda fisiológica do organismo, elas devem ser obtidas da dieta e, embora os suplementos vitamínicos correspondam à pequena porcentagem da fórmula (0,1 a 0,5%), as vitaminas podem representar de 1-3% do custo da ração, sendo que a A e E chegam a corresponder a 50% do custo total do suplemento vitamínico (TOLEDO et al, 2006).…”
unclassified